Measurement on the desorption yields of ceramic and Au-coated ceramic irradiated with Bi32+ and Xe23+. (December 2021) - Xie, W.J.; Meng, J.; Li, C.C.; Jiao, J.Q.; Chai, Z.; Luo, C.; Yang, W.S.; Shen, G.D.; Li, Z.S.; Zhou, D.T.; Liu, J.L.; Lin, X.J.; et al.
Abstract: The Booster Ring (BRing) is the key part of the High Intensity Heavy Ion Accelerator Facility (HIAF). In order to reduce the eddy current effect, specifically developed stainless steel vacuum chambers with ultra-thin (0.3 mm) walls and ceramic spacers will be used. Desorption yields experiments were carried out on spacers made of zirconia ceramic, on zirconia ceramic coated with different Au thicknesses and coating processes, as well as on zirconia ceramic coated with getter films. A dedicated mass spectrometer was used to analyze the changes in the gas composition during the bombardment. The results show that Au-coated zirconia ceramic can effectively lower the desorption yields, the higher the Au coating thickness, the lower the desorption yield. When the beam impinges on the surface of the zirconia ceramic, the pressure randomly fluctuates, without showing any clear long term beam cleaning effect. As far as the coating process is concerned, samples coated by magnetron sputtering show higher desorption yields than those electroplated. However, the electroplating process is characterized by a low bonding force between the films and the ceramic substrate, which makes possible for the film to peel off under beam bombardment. Finally, TiN-coated zirconia ceramic has better static vacuum performances. However, due to its strong H2 absorption capacity, TiN coated samples will release more H2 under bombardment, thus providing a worse dynamic vacuum conditions. Practical consequences for the BRing vacuum system of the HIAF are given. Highlights: Desorption yields of ceramic and Au coated ceramic irradiated by Bi 32+ and Xe 23+ were measured. Ceramic has no obvious beam cleaning effect during beam bombardment. With the increase of Au coating thickness, the desorption yields decreases. The magnetron sputtering Au coating process has a higher desorption yields than electroplating. TiN-coated ceramic has a higher desorption yields than Au coated ceramic.